Silk fibroin nanoparticle injection as well as preparation method and application thereof
By mixing silk fibroin nanoparticles with hyaluronic acid or its salt solution to form a stable injection solution, the problems of chemical additive use, poor water solubility and difficult to regulate the degradation rate in the prior art are solved, and the stability and safety of the system are achieved.
Patent Information
- Application Number
- CN202411794472.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-04-11
AI Technical Summary
The existing silk fibroprotein granules and hyaluronic acid complex systems require chemical additives, which are poor in water solubility, are prone to aggregation, and are difficult to regulate the degradation rate.
The injection solution of silk fibroin nanoparticles is formed by adding silk fibroin nanoparticles to deionized water and mixing them with hyaluronic acid or its salt solution in a certain proportion. This system forms physical crosslinking through hydrogen bonding, which is stable and difficult to aggregate, and has no other chemical additives. The degradation products are amino acids and polysaccharides, which have the advantages of safety and harm.
The stability and injectability of the system are achieved, the use of chemical additives is avoided, the degradation products are safe and harmless, and the degradation rate of silk fibroin nanoparticles can be adjusted.
Smart Images

Figure CN119792193A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biomedical technology, and in particular to a silk fibroin nanoparticle injection, a preparation method and application thereof. Background Art
[0002] Nanotechnology has been widely studied in different fields of application. In the medical field, new nanoparticles have been developed as injectable drug carriers for the treatment of many diseases. In the field of medical beauty, nano-scale skin treatment products have smaller particles and can be more evenly distributed under the skin. They also have advantages such as high transparency and less clogging of pores, making the products feel more refreshing and comfortable. Therefore, nanoparticle preparations have aroused great interest as injectable therapeutic agents and fillers.
[0003] Silk fibroin and hyaluronic acid are both natural biodegradable medical polymers with good biocompatibility and degradability. They have been widely used as biomaterials in the field of biomedical materials.
[0004] At present, most of the silk fibroin / hyaluronic acid injection systems are based on silk fibroin solution and hyaluronic acid or its salt solution, and most of them involve the addition of chemical crosslinking agents. For example, the patent with publication number CN117599247A discloses a preparation method and application of a silk fibroin microcarrier skin filling preparation, wherein mulberry silk is degummed, concentrated, and dried to obtain dry silk fibroin; the dry silk fibroin is configured into an aqueous solution, the solution is mixed with vitamin C, stirred, and freeze-dried to obtain VC-loaded silk fibroin; the VC-loaded silk fibroin is configured into a silk fibroin solution, the silk fibroin solution, hyaluronic acid, maltodextrin and a crosslinking agent are mixed, and the mixture is allowed to stand at 35-40°C to obtain a composite gel, which is sterilized to obtain a silk fibroin microcarrier skin filling preparation. The silk fibroin prepared by this method is converted into Silk II after concentration, and the system is doped with a crosslinking agent sodium octyl sulfate aqueous solution, which has slight toxicity, and the degradation products will remain in the body and are not easily absorbed by the body, and the biological safety needs to be improved.
[0005] At present, there are also a few silk fibroin / hyaluronic acid injection systems that are prepared based on silk fibroin particles and hyaluronic acid or its salt solution. However, most of the existing silk fibroin particles and hyaluronic acid compound systems involve the addition of chemical crosslinkers or chemical reagents, which are irritating to the body; they have poor water solubility, are easy to aggregate, and have poor injection efficacy; and most of the silk fibroin nanoparticles are silk II structures, and the degradation rate is difficult to control. Summary of the invention
[0006] In view of the technical problems existing in the background technology, the present application provides a silk fibroin nanoparticle injection and its preparation method and application, aiming to solve the problems that the existing silk fibroin particle and hyaluronic acid compound system requires chemical additives, has poor water solubility, is easy to aggregate, and the degradation rate is difficult to control.
[0007] In a first aspect, the present application provides a method for preparing a silk fibroin nanoparticle injection, comprising the following steps:
[0008] S1. The silk fibroin solution is frozen and solidified by liquid nitrogen to obtain a silk fibroin frozen body, and then annealed, thawed, filtered and freeze-dried to obtain a silk fibroin nanoparticle powder;
[0009] S2. adding the silk fibroin nanoparticle powder to deionized water and dispersing the powder evenly to obtain a silk fibroin nanoparticle suspension;
[0010] S3. Mixing hyaluronic acid or a salt thereof with deionized water to obtain a hyaluronic acid or a salt solution thereof;
[0011] S4. Add the silk fibroin nanoparticle suspension to the hyaluronic acid or its salt solution, mix well, and prepare the silk fibroin nanoparticle injection.
[0012] In the technical scheme of the embodiment of the present application, by adding the obtained silk fibroin nanoparticles to deionized water, after making suspension, mixed with hyaluronic acid or its saline solution in a certain proportion, the injection of silk fibroin nanoparticles is obtained. The silk fibroin nanoparticles in the injection of the silk fibroin nanoparticles obtained in the present application are silk I structures rich in carboxyl and amino, by mixing with hyaluronic acid or its saline solution of a specific ratio, a large amount of hydrogen bonds are formed between molecules to form physical crosslinks, the system is stable, not easy to aggregate, and the addition of silk fibroin nanoparticles improves the degradation resistance of hyaluronic acid or its saline solution, hyaluronic acid or its saline solution to the encapsulation of silk fibroin nanoparticles, and the dispersion stability of silk fibroin nanoparticles can be enhanced, and the two act together to improve the system stability, so as to obtain good stability, and have good injectability. In addition, the silk fibroin nanoparticle injection is without other chemical additives, and the degradation product is amino acid and polysaccharide, with the advantage of safety and harmlessness.
[0013] In some embodiments, in step S1, the concentration of the silk fibroin solution is 0.1-5.0%; the annealing temperature is -10-0°C, and the annealing time is 8-96h;
[0014] In this embodiment, the silk fibroin treated under this condition has a Silk I structure.
[0015] In some embodiments, in step S1, the silk fibroin solution may be treated with a drug.
[0016] In this embodiment, the silk fibroin nanoparticle injection made of silk fibroin treated with drug has the effect of local delivery and sustained release of medical drugs.
[0017] In some embodiments, in step S2, the concentration of the silk fibroin nanoparticle suspension is 0.1% to 6%.
[0018] In this embodiment, silk fibroin nanoparticles are made into a suspension of a specific concentration and mixed with a hyaluronic acid or its salt solution of a specific concentration. A large number of hydrogen bonds are generated between the molecules to form physical crosslinks, so that the mixed solution forms a stable mixture system. The addition of silk fibroin nanoparticles improves the degradation resistance of hyaluronic acid or its salt solution.
[0019] In some embodiments, in step S2, the dispersion method is ultrasonic treatment; the power of the ultrasonic treatment is 50 to 200 W; and the time of the ultrasonic treatment is 2 to 15 min.
[0020] In this embodiment, the silk fibroin nanoparticles are evenly dispersed by ultrasonic treatment. However, if the ultrasonic treatment time is too long or the ultrasonic power is too high, the silk fibroin nanoparticles will be broken.
[0021] In some embodiments, in step S3, the concentration of the hyaluronic acid or its salt solution is 1.5% to 2.0%; the average molecular weight of the hyaluronic acid or its salt is 300 to 3000 kDa.
[0022] In this embodiment, by making hyaluronic acid or its salt into a solution of specific concentration and mixing it with a silk fibroin suspension of specific concentration, a large number of hydrogen bonds are generated between molecules to form physical crosslinks, so that the mixed solution forms a stable mixture system, and the hyaluronic acid or its salt solution can form a coating on the silk fibroin nanoparticles, thereby enhancing the dispersion stability of the silk fibroin nanoparticles. If the molecular weight of sodium hyaluronate or its salt is too large and the concentration of the solution is too high, the solution will be too viscous, making it difficult for the silk fibroin suspension to mix evenly with it, and it will also be difficult to form a coating on the silk fibroin suspension, so that the mixed solution cannot form a stable mixture system. If the molecular weight of sodium hyaluronate or its salt is too small and the concentration of the solution is too low, the solution will be too fluid, making it difficult to effectively coat the silk fibroin suspension, so that the mixed solution cannot form a stable mixture system.
[0023] In some embodiments, in step S4, in the silk fibroin nanoparticle injection, the mass of the silk fibroin nanoparticles accounts for 1-50 wt % of the mass of the hyaluronic acid or its salt.
[0024] In this embodiment, in a mixture of silk fibroin nanoparticles and hyaluronic acid or its salt in a specific ratio, the molecules of the two form physical cross-links through a large number of hydrogen bonds, the system is stable and not easy to aggregate, and the addition of silk fibroin nanoparticles improves the degradation resistance of hyaluronic acid or its salt solution. The wrapping of silk fibroin nanoparticles by hyaluronic acid or its salt solution can enhance the dispersion stability of silk fibroin nanoparticles. The combined effect of the two improves the stability of the system, thereby achieving both good stability and good injectability.
[0025] In some embodiments, in step S4, the mixing method is a homogenizer treatment; the homogenization treatment time is 5 to 15 minutes.
[0026] In this embodiment, the mixed solution of silk fibroin nanoparticles / hyaluronic acid or its salt is processed by a homogenizer so that the two can be better mixed and uniform.
[0027] In the second aspect, an embodiment of the present application provides a silk fibroin nanoparticle injection, which is prepared by the preparation method of the silk fibroin nanoparticle injection described in any one of claims 1 to 8, and includes silk fibroin nanoparticles, hyaluronic acid or its salt and deionized water; the silk fibroin nanoparticles are Silk I structure.
[0028] In the technical solution of the embodiment of the present application, the prepared silk fibroin nanoparticle injection has a stable system and is not easy to aggregate. The silk fibroin nanoparticles have a Silk I structure, and their degradation rate can be adjusted by the annealing treatment time.
[0029] In a third aspect, an embodiment of the present application provides an application of a silk fibroin nanoparticle injection, and the silk fibroin nanoparticle injection is applied in the medical field.
[0030] In the technical solution of the embodiment of the present application, the silk fibroin nanoparticle injection has no added chemical reagents, has good biosafety, and is not prone to aggregation, and can be used for cosmetic filling and local delivery and sustained release of medical drugs.
[0031] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0033] Figure 1 These are the SEM images and XRD images of the rhodamine B-loaded silk fibroin nanoparticles prepared in Example 1.
[0034] Figure 2 This is a fluorescence microscopy image of the silk fibroin nanoparticle suspension loaded with rhodamine B prepared in Example 1.
[0035] Figure 3 This is a laser confocal image of the silk fibroin nanoparticle injection solution loaded with rhodamine B prepared in Example 1.
[0036] Figure 4 It is a diagram showing the injection effect of the silk fibroin nanoparticle injection solution loaded with rhodamine B prepared in Examples 1 to 4 and Comparative Examples 1 to 2.
[0037] Figure 5 These are laser confocal images of the silk fibroin nanoparticle injections loaded with rhodamine B prepared in Examples 5-6 and Comparative Examples 3-4.
[0038] Figure 6 These are laser confocal images and SEM images of the silk fibroin nanoparticle injection solution loaded with rhodamine B prepared in Example 1 and Comparative Example 3 after standing at room temperature for 14 days.
[0039] Figure 7 The rheological graphs of the silk fibroin nanoparticle injection solution loaded with rhodamine B prepared in Example 1 and Comparative Example 5 on the same day and after standing at room temperature for 14 days.
[0040] Figure 8 This is a laser confocal image of the silk fibroin nanoparticle injection solution loaded with rhodamine B prepared in Comparative Example 6 after standing at room temperature for 14 days.
[0041] Fig. 9 This is a laser confocal image of the silk fibroin nanoparticle injection solution loaded with rhodamine B prepared in Comparative Example 7.
[0042] Fig.10 This is a laser confocal image of the silk fibroin nanoparticle injection solution loaded with rhodamine B prepared in Comparative Examples 8 and 9.
[0043] Fig.11 It is a degradation diagram of the silk fibroin nanoparticles loaded with rhodamine B prepared in Examples 2, 7-8 and Comparative Examples 10-11. DETAILED DESCRIPTION
[0044] The following is a detailed description of the embodiments of the technical solution of the present application. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0045] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms "including" and "having" and any variations thereof used herein are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0046] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0047] In order to solve the problems that the existing silk fibroin protein particle and hyaluronic acid compound system requires chemical additives, has poor water solubility, is easy to aggregate, and the degradation rate is difficult to control, the present application provides a silk fibroin protein nanoparticle injection and its preparation method and application. The prepared silk fibroin protein nanoparticles are added to deionized water to make a suspension, and then mixed with hyaluronic acid or its salt solution in a certain proportion to prepare an injection of silk fibroin protein nanoparticles. The molecules of the injection of silk fibroin protein nanoparticles prepared in the present application form physical cross-links through a large number of hydrogen bonds, and the system is stable and not easy to aggregate; and the silk fibroin protein nanoparticle injection does not have other chemical additives, and the degradation products are amino acids and polysaccharides, which has the advantages of safety and harmlessness; in addition, the silk fibroin in the silk fibroin protein nanoparticle injection is a Silk I structure, and the degradation rate can be regulated as needed. Compared with the gel of simple cross-linking of traditional hyaluronic acid, the addition of silk protein nanoparticles increases the strength of hyaluronic acid, so that the degradation resistance of hyaluronic acid is improved. At the same time, due to the encapsulation of hyaluronic acid or its salt solution on silk protein nanoparticles, the body will first absorb and degrade the hyaluronic acid or its salt of the outer layer, and then absorb and degrade the silk protein nanoparticles. The two work together to effectively slow down the degradation rate of the composite gel, prolong the tissue repair and filling time of the system, improve the effectiveness of the material, and obtain the effect of long-term beauty. And in the degradation process, due to the encapsulation of hyaluronic acid or its salt, the medicine in the nanoparticles will always be slowly released, so that the medicine will not be absorbed by the body in large quantities and quickly, and the medicine will not be diffused to a large range around it but confined to a specific area, and local drug sustained release can be successfully achieved, reducing the number of injections; due to the encapsulation of hyaluronic acid, silk protein nanoparticles will not produce a large amount of aggregation, thereby reducing the discomfort caused by the swelling and hardening of the body caused by particle aggregation. The silk protein nanoparticle injection prepared by the present invention has a simple process and good biosafety, and can be used for local delivery and sustained release of cosmetic filling and medical drugs.
[0048] On the one hand, the present application provides a method for preparing a silk fibroin nanoparticle injection, comprising the following steps:
[0049] S1. The silk fibroin solution is frozen and solidified by liquid nitrogen to obtain a silk fibroin frozen body, and then annealed, thawed, filtered and freeze-dried to obtain a silk fibroin nanoparticle powder;
[0050] S2. adding the silk fibroin nanoparticle powder to deionized water and dispersing the powder evenly to obtain a silk fibroin nanoparticle suspension;
[0051] S3. Mixing hyaluronic acid or a salt thereof with deionized water to obtain a hyaluronic acid or a salt solution thereof;
[0052] S4. Add the silk fibroin nanoparticle suspension to the hyaluronic acid or its salt solution, mix well, and prepare the silk fibroin nanoparticle injection.
[0053] In the technical scheme of the embodiment of the present application, by adding the obtained silk fibroin nanoparticles to deionized water, after making suspension, mixed with hyaluronic acid or its saline solution in a certain proportion, the injection of silk fibroin nanoparticles is obtained. The silk fibroin nanoparticles in the injection of the silk fibroin nanoparticles obtained in the present application are silk I structures rich in carboxyl and amino, by mixing with hyaluronic acid or its saline solution of a specific ratio, a large amount of hydrogen bonds are formed between molecules to form physical crosslinks, the system is stable, not easy to aggregate, and the addition of silk fibroin nanoparticles improves the degradation resistance of hyaluronic acid or its saline solution, hyaluronic acid or its saline solution to the encapsulation of silk fibroin nanoparticles, and the dispersion stability of silk fibroin nanoparticles can be enhanced, and the two act together to improve the system stability, so as to obtain good stability, and have good injectability. In addition, the silk fibroin nanoparticle injection is without other chemical additives, and the degradation product is amino acid and polysaccharide, with the advantage of safety and harmlessness.
[0054] Furthermore, in some embodiments, in step S1, the concentration of the silk fibroin solution is 0.1-5.0%; the annealing temperature is -10-0°C, and the annealing time is 8-96h.
[0055] In the technical solution of the embodiment of the present application, the silk fibroin treated under this condition has a Silk I structure.
[0056] Furthermore, in some embodiments, the annealing treatment time is 12 to 48 hours.
[0057] In the technical solution of the embodiment of the present application, the degradation rate of the silk fibroin nanoparticle powder can be regulated by performing annealing treatment within this time range.
[0058] Furthermore, in some embodiments, in step S1, the silk fibroin solution may be treated with drug loading.
[0059] In the technical solution of the embodiment of the present application, the silk fibroin nanoparticle injection made of silk fibroin treated with drug has the effect of local delivery and sustained release of medical drugs.
[0060] Furthermore, in some embodiments, the drug loading treatment step is: treating the silk fibroin solution and the drug in a co-bath; in the drug loading treatment, the mass of the drug accounts for 1wt% to 100wt% of the mass of the silk fibroin.
[0061] In the technical solution of the embodiment of the present application, the drug can be effectively loaded on the silk fibroin by co-bathing with the drug.
[0062] Furthermore, in some embodiments, in step S2, the dispersion method is ultrasonic treatment; the power of the ultrasonic treatment is 50 to 200 W; and the time of the ultrasonic treatment of the silk fibroin nanoparticle suspension is 2 to 15 min.
[0063] In the technical solution of the embodiment of the present application, the silk fibroin nanoparticles can be evenly dispersed through ultrasonic treatment.
[0064] Furthermore, in some embodiments, the ultrasonic treatment time of the drug-loaded silk fibroin nanoparticle suspension is 2 to 5 minutes.
[0065] In the technical solution of the embodiment of the present application, the drug-loaded silk fibroin nanoparticles are evenly dispersed through ultrasonic treatment. If the ultrasonic treatment time is too long, it will lead to poor drug loading effect.
[0066] Furthermore, in some embodiments, in step S2, the concentration of the silk fibroin nanoparticle suspension is 0.4% to 6%.
[0067] In the technical solution of the embodiment of the present application, silk fibroin nanoparticles are made into a suspension of a specific concentration and mixed with hyaluronic acid or its salt solution of a specific concentration. A large number of hydrogen bonds are generated between the molecules to form physical cross-links, so that the mixed solution forms a stable mixture system, and the addition of silk fibroin nanoparticles improves the degradation resistance of hyaluronic acid or its salt solution.
[0068] Furthermore, in some embodiments, in step S3, the concentration of the hyaluronic acid or its salt solution is 1.5% to 2.0%; and the average molecular weight of the hyaluronic acid or its salt is 300 to 3000 kDa.
[0069] In the technical solution of the embodiment of the present application, hyaluronic acid or its salt is made into a solution of a specific concentration and mixed with a silk fibroin suspension of a specific concentration, a large number of hydrogen bonds are generated between molecules to form physical cross-links, so that the mixed solution forms a stable mixture system, and the hyaluronic acid or its salt solution can form a coating on the silk fibroin nanoparticles, thereby enhancing the dispersion stability of the silk fibroin nanoparticles. If the molecular weight of sodium hyaluronate or its salt is too large and the concentration of the solution is too high, the solution will be too viscous, making it difficult for the silk fibroin suspension to mix evenly with it, and it will also be difficult to form a coating on the silk fibroin suspension, so that the mixed solution cannot form a stable mixture system. If the molecular weight of sodium hyaluronate or its salt is too small and the concentration of the solution is too low, the solution fluidity will be too strong, making it difficult to effectively coat the silk fibroin suspension, so that the mixed solution cannot form a stable mixture system.
[0070] Furthermore, in some embodiments, in step S4, the mixing method is a homogenizer treatment; and the homogenization treatment time is 5 to 15 minutes.
[0071] In the technical solution of the embodiment of the present application, the mixed solution of silk fibroin nanoparticles / hyaluronic acid or its salt is treated by a homogenizer so that the two can be better mixed and uniform.
[0072] In the second aspect, an embodiment of the present application provides a silk fibroin nanoparticle injection, which is prepared by the preparation method of the silk fibroin nanoparticle injection described in any one of claims 1 to 8, and includes silk fibroin nanoparticles, hyaluronic acid or its salt and deionized water; the silk fibroin nanoparticles are Silk I structure.
[0073] In the technical solution of the embodiment of the present application, the prepared silk fibroin nanoparticle injection has a stable system and is not easy to aggregate. The silk fibroin nanoparticles have a Silk I structure, and their degradation rate can be adjusted by the annealing treatment time.
[0074] In a third aspect, an embodiment of the present application provides an application of a silk fibroin nanoparticle injection, and the silk fibroin nanoparticle injection is applied in the medical field.
[0075] In the technical solution of the embodiment of the present application, the silk fibroin nanoparticle injection has no added chemical reagents, has good biosafety, and is not prone to aggregation, and can be used for cosmetic filling and local delivery and sustained release of medical drugs.
[0076] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0077] Example 1
[0078] This embodiment provides a method for preparing a silk fibroin nanoparticle injection, which specifically comprises the following steps:
[0079] (1) 100 g of mulberry silk was immersed in 5 L of 0.05% NaCO3 solution, and the solution was boiled at 100°C for 30 min, which was repeated 3 times to degummed the silk, and then the pure silk fiber was obtained after being fully washed and dried; the silk fiber was added to a ternary solution of CaCl2 / CH3CH2OH / H2O with a molar ratio of 1:2:8, and the solution was stirred and dissolved at 72°C for 1 h to obtain a silk fibroin mixed solution; the obtained silk fibroin mixed solution was placed in a dialysis bag, dialyzed with deionized water for 3 days, and filtered with gauze to obtain a silk fibroin solution, and then the obtained silk fibroin solution was poured into a centrifuge tube, and the silk fibroin solution was obtained after centrifugation.
[0080] (2) The silk fibroin solution was diluted to a concentration of 1% and poured into a beaker. Rhodamine B (a fluorescent imaging drug) accounting for 20 wt% of the silk fibroin solution was then added. The solution was then magnetically stirred until the Rhodamine B was completely dissolved. The solution was then placed in liquid nitrogen at -196°C for complete freezing. The solution was then transferred to a refrigerator at -4°C for annealing for 48 h. The solution was then placed in an oven at 37°C for thawing. The insoluble matter was then filtered out with a filter. The resulting solution was then placed in liquid nitrogen for complete freezing. The solution was then placed in a dryer for drying to obtain silk fibroin nanoparticle powder loaded with Rhodamine B.
[0081] (3) 10% of the mass of the hyaluronic acid solution was mixed with silk fibroin nanoparticle powder loaded with rhodamine B and deionized water, and the mixture was subjected to ultrasonic treatment at a power of 100 W for 5 min to obtain a suspension of silk fibroin nanoparticles loaded with rhodamine B at a concentration of 1.3%.
[0082] (4) Hyaluronic acid with a molecular weight of 1370 kDa was added to deionized water and dissolved for 12 h to obtain a hyaluronic acid solution with a concentration of 1.5%.
[0083] (5) The obtained suspension of silk fibroin nanoparticles loaded with rhodamine B was added to the hyaluronic acid solution and homogenized for 15 minutes using a 4-speed homogenizer to obtain an injection of silk fibroin nanoparticles loaded with rhodamine B.
[0084] The SEM and XRD images of the silk fibroin nanoparticle powder loaded with rhodamine B prepared in this example are as follows: Figure 1 shown.
[0085] Depend on Figure 1 It can be seen from the SEM image that the silk fibroin nanoparticles loaded with rhodamine B are regular spherical, and the particle size is between 500nm and 1000nm. The addition of rhodamine B does not destroy the morphology of the silk fibroin nanoparticles. It can be seen from the XRD image that the prepared drug-loaded silk fibroin nanoparticles are Silk I structures.
[0086] The suspension of silk fibroin nanoparticles loaded with rhodamine B prepared in this example was dropped onto a glass slide and then observed under a fluorescence microscope. Figure 2 shown.
[0087] Depend on Figure 2 It can be seen that the silk fibroin nanoparticles loaded with rhodamine B still maintain a spherical shape, proving that the ultrasonic treatment did not cause the sample to break.
[0088] The laser confocal image of the silk fibroin nanoparticle injection solution loaded with rhodamine B prepared in this example is as follows: Figure 3 shown.
[0089] Depend on Figure 3 It can be seen that the silk fibroin nanoparticle injection solution loaded with rhodamine B prepared in this example has good dispersibility.
[0090] Examples 2 to 4 and Comparative Examples 1 to 2
[0091] Examples 2 to 4 and Comparative Examples 1 to 2 respectively provide a method for preparing a silk fibroin nanoparticle injection. Compared with Example 1, the difference is that the amount of silk fibroin nanoparticle powder loaded with rhodamine B is different. The specific amount is shown in Table 1. The other steps are roughly the same as Example 1 and will not be repeated here.
[0092] Table 1 Amount of silk fibroin nanoparticle powder loaded with rhodamine B in Examples 2 to 4 and Comparative Examples 1 to 2
[0093]
[0094] The silk fibroin nanoparticle injections prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were injected using a 27 g needle. Figure 4 shown.
[0095] Depend on Figure 4 It can be seen that the injection solutions prepared in Examples 1 to 4 have good injectability; the silk fibroin nanoparticle injection solution prepared in Comparative Example 1 can also be injected, but since the amount of silk fibroin nanoparticles loaded is too small, it has no practical usable value; the silk fibroin nanoparticle injection solution prepared in Comparative Example 2 cannot be injected, because the amount of silk fibroin nanoparticles loaded is too much, the particles are obvious, resulting in a large push force and clogging of the needle.
[0096] Examples 5-6 and Comparative Examples 3-4
[0097] Examples 5 to 6 and Comparative Examples 3 to 4 respectively provide a method for preparing a silk fibroin nanoparticle injection. Compared with Example 1, the difference is that the concentration of the hyaluronic acid solution and the average molecular weight of hyaluronic acid are different, as shown in Table 2. The other steps are roughly the same as Example 1 and will not be repeated here.
[0098] Table 2 Concentration of hyaluronic acid solution and average molecular weight of hyaluronic acid in Examples 5-6 and Comparative Examples 3-4
[0099]
[0100] The laser confocal images of the silk fibroin nanoparticle injections prepared in Examples 5-6 and Comparative Examples 3-4 are as follows: Figure 5 shown.
[0101] Depend on Figure 5 It can be seen that the dispersion effect of silk fibroin nanoparticles in the silk fibroin nanoparticle injections prepared in Examples 5 to 6 is better, while the dispersion effect of silk fibroin nanoparticles in the silk fibroin nanoparticle injections prepared in Comparative Example 4 is not very good. This is because the viscosity of the hyaluronic acid solution is too high and the silk fibroin nanoparticles are difficult to disperse therein.
[0102] After the silk fibroin nanoparticle injections prepared in Example 1 and Comparative Example 3 were left standing at room temperature for 14 days, laser confocal images and SEM images were taken, respectively. Figure 6 shown.
[0103] Depend on Figure 6 It can be seen that the stability of the silk fibroin nanoparticle injection prepared in Comparative Example 3 is worse than that of the silk fibroin nanoparticle injection prepared in Example 1. This is because the viscosity of hyaluronic acid is too low. Although the silk fibroin nanoparticles can be well dispersed in the early stage, their fluidity is too large in the later stage, and the encapsulation constraint of the nanoparticles is poor, and the silk fibroin nanoparticles are easily aggregated again; for the electron micrographs, both show a well-formed spherical shape at 14 days, proving that the silk fibroin nanoparticles are well protected in hyaluronic acid and have not been degraded. For the drug-loaded silk fibroin nanoparticles, it is proved that the drug can be released slowly all the time without sudden release.
[0104] Comparative Example 5
[0105] This comparative example provides a method for preparing a silk fibroin nanoparticle injection. Compared with Example 1, the difference is that no silk fibroin nanoparticles are added, that is, step (1), step (2), step (3) and step (5) are not performed (i.e., pure sodium hyaluronate solution), and the other steps are roughly the same as Example 1 and will not be repeated here.
[0106] The rheological diagrams of the injections prepared in Example 1 and Comparative Example 5 were tested on the same day and after standing at room temperature for 14 days. Figure 7 shown.
[0107] from Figure 7It can be seen that the injections prepared in Example 1 and Comparative Example 5 were both in a non-flowing state on the same day. After standing for 14 days, the viscosity of the injection prepared in Comparative Example 5 was greatly reduced, and the solution became a flowing state, while the viscosity of the injection prepared in Example 1 was reduced, but part of it was still in a non-flowing state. This is because the addition of silk fibroin nanoparticles can enhance the strength of hyaluronic acid or its salt solution and delay its degradation.
[0108] Comparative Example 6
[0109] This comparative example provides a method for preparing a silk fibroin nanoparticle injection. Compared with Example 1, the difference is that hyaluronic acid is not added, that is, step (4) and step (5) are not performed (i.e., pure silk fibroin nanoparticle solution), and the other steps are roughly the same as Example 1 and will not be repeated here.
[0110] The injection prepared in this comparative example was left to stand at room temperature for 14 days, and then a laser confocal image was taken. Figure 8 shown.
[0111] Depend on Figure 8 and Figure 6 It can be seen that after 14 days of placement, the degree of spontaneous aggregation of the silk fibroin nanoparticles in the injection solution prepared in Comparative Example 6 is much higher than that in Example 1. This is because the hyaluronic acid solution can protect the silk fibroin nanoparticles, alleviate the aggregation of the silk fibroin nanoparticles, and prolong the stability of the system.
[0112] Comparative Example 7
[0113] This comparative example provides a method for preparing a silk fibroin nanoparticle injection. Compared with Example 1, the difference is that in step (3), the silk fibroin nanoparticle powder loaded with rhodamine B and deionized water are magnetically stirred for 5 minutes, and the other steps are roughly the same as Example 1 and will not be repeated here.
[0114] The laser confocal image of the silk fibroin nanoparticle injection prepared in this comparative example is as follows: Fig. 9 shown.
[0115] Compared with the laser confocal image of the silk fibroin nanoparticle injection prepared in Example 1, it can be seen that the ordinary stirring method for treating the silk fibroin nanoparticles without ultrasonic treatment cannot achieve a good dispersion effect.
[0116] Comparative Examples 8 to 9
[0117] Comparative Examples 8 to 9 respectively provide a method for preparing a silk fibroin nanoparticle injection. Compared with Example 1, the difference is that the mixing method of silk fibroin nanoparticles and hyaluronic acid is different. In Comparative Example 8, step (3) is not performed, but the silk fibroin nanoparticles are directly added to the hyaluronic acid solution; in Comparative Example 9, step (4) is not performed, but hyaluronic acid powder is added to the silk fibroin nanoparticle suspension. The other steps are roughly the same as in Example 1 and are not repeated here.
[0118] The laser confocal images of the silk fibroin nanoparticle injections prepared in Comparative Examples 8 and 9 are as follows: Fig.10 shown.
[0119] Depend on Figure 3 and Fig.10 It can be seen that the dispersion effect of the silk fibroin nanoparticle injection prepared by the methods in Comparative Examples 8 and 9 is poorer than that in Example 1.
[0120] Embodiment 7-8
[0121] Examples 7 to 8 and comparative examples 10 to 11 respectively provide a method for preparing a silk fibroin nanoparticle injection. Compared with Example 1, the difference is that in step (2), the annealing time of Example 7 is 12 hours; the annealing time of Example 8 is 24 hours. The other steps are roughly the same as those of Example 1 and will not be repeated here.
[0122] The silk fibroin nanoparticles prepared in Examples 2, 7-8 were subjected to degradation experiments in PBS buffer. The degradation diagram is shown in FIG. Fig.11 shown.
[0123] Depend on Fig.11 It can be seen that the degradation rate of the silk fibroin nanoparticles prepared in Examples 2 and 7-8 decreases with the increase of the heating treatment time, indicating that when the annealing time is 12 to 48 hours, the degradation rate of the silk fibroin nanoparticles with Silk I structure can be effectively regulated.
[0124] In summary, the present application provides a silk fibroin nanoparticle injection or its preparation method and application, which belongs to the field of biomedical technology. The prepared silk fibroin nanoparticles are added to deionized water to make a suspension, and then mixed with hyaluronic acid or its salt solution in a certain proportion to prepare an injection of silk fibroin nanoparticles. The molecules of the injection of silk fibroin nanoparticles prepared in the present application form physical cross-links through a large number of hydrogen bonds, and the system is stable and not easy to aggregate; and the silk fibroin nanoparticle injection does not contain other chemical additives, and the degradation products are amino acids and polysaccharides, which has the advantages of safety and harmlessness; in addition, the silk fibroin in the silk fibroin nanoparticle injection is a Silk I structure, and the degradation rate can be regulated as needed. Compared with the gel of simple cross-linking of traditional hyaluronic acid, the addition of silk protein nanoparticles increases the strength of hyaluronic acid, so that the degradation resistance of hyaluronic acid is improved. At the same time, due to the encapsulation of hyaluronic acid or its salt solution on silk protein nanoparticles, the body will first absorb and degrade the hyaluronic acid or its salt of the outer layer, and then absorb and degrade the silk protein nanoparticles. The two work together to effectively slow down the degradation rate of the composite gel, prolong the tissue repair and filling time of the system, improve the effectiveness of the material, and obtain the effect of long-term beauty. And in the degradation process, due to the encapsulation of hyaluronic acid or its salt, the medicine in the nanoparticles will always be slowly released, so that the medicine will not be absorbed by the body in large quantities and quickly, and the medicine will not be diffused to a large range around it but confined to a specific area, and local drug sustained release can be successfully achieved, reducing the number of injections; due to the encapsulation of hyaluronic acid, silk protein nanoparticles will not produce a large amount of aggregation, thereby reducing the discomfort caused by the swelling and hardening of the body caused by particle aggregation. The silk protein nanoparticle injection prepared by the present invention has a simple process and good biosafety, and can be used for local delivery and sustained release of cosmetic filling and medical drugs.
[0125] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A method for preparing a silk fibroin nanoparticle injection, characterized in that: The following steps are involved: S1. The silk fibroin solution is frozen and solidified by liquid nitrogen to obtain a silk fibroin frozen body, and then annealed, thawed, filtered and freeze-dried to obtain a silk fibroin nanoparticle powder; S2. adding the silk fibroin nanoparticle powder to deionized water and dispersing the powder evenly to obtain a silk fibroin nanoparticle suspension; S3. Mixing hyaluronic acid or a salt thereof with deionized water to obtain a hyaluronic acid or a salt solution thereof; S4. Add the silk fibroin nanoparticle suspension to the hyaluronic acid or its salt solution, mix well, and prepare the silk fibroin nanoparticle injection.
2. The method for preparing the silk fibroin nanoparticle injection according to claim 1, characterized in that: In step S3, the concentration of the hyaluronic acid or its salt solution is 1.5-2.0%; the average molecular weight of the hyaluronic acid or its salt is 300-3000 kDa.
3. The method for preparing the silk fibroin nanoparticle injection according to claim 1, characterized in that: In step S4, in the silk fibroin nanoparticle injection, the mass of the silk fibroin nanoparticles accounts for 1 to 50 wt % of the mass of the hyaluronic acid or its salt.
4. The method for preparing the silk fibroin nanoparticle injection according to claim 1, characterized in that: In step S1, the concentration of the silk fibroin solution is 0.1-5.0%; the annealing temperature is -10-0°C, and the annealing time is 8-96h.
5. The method for preparing the silk fibroin nanoparticle injection according to claim 1, characterized in that: In step S1, the silk fibroin solution may be treated with drug loading.
6. The method for preparing the silk fibroin nanoparticle injection according to claim 1, characterized in that: In step S2, the concentration of the silk fibroin nanoparticle suspension is 0.1% to 6%.
7. The method for preparing the silk fibroin nanoparticle injection according to claim 1, characterized in that: In step S2, the dispersion method is ultrasonic treatment; the power of the ultrasonic treatment is 50 to 200 W; and the time of the ultrasonic treatment is 2 to 15 minutes.
8. The method for preparing the silk fibroin nanoparticle injection according to claim 1, characterized in that: In step S4, the mixing method is a homogenizer treatment; the homogenization treatment time is 5 to 15 minutes.
9. A silk fibroin nanoparticle injection, characterized in that: The silk fibroin nanoparticle injection is prepared by the preparation method of any one of claims 1 to 8, comprising silk fibroin nanoparticles, hyaluronic acid or its salt and deionized water; the silk fibroin nanoparticles are of SilkI structure.
10. An application of a silk fibroin nanoparticle injection, characterized in that: The silk fibroin nanoparticle injection described in claim 9 is used in the medical field.
Citation Information
Patent Citations
Silk fibroin microcarrier skin filling preparation as well as preparation method and application thereof
CN117599247A